ANALISIS PENGARUH SUKU BUNGA, VOLUME PERDAGANGAN DAN KURS TERHADAP RETURN SAHAM SEKTOR PROPERTI YANG LISTED DI BEI (Studi Kasus Pada Saham Sektor Properti yang Listed di BEI Periode 2003-2007) - Fuadi, Dheny Wahyu (JURNAL BISNIS STRATEGI, 2009)
The capital market is one of investment alternative that able to yield optimal advantage for investor. Each investor is requiring of relevant information with transaction development in stock. This is very important to be made in consideration in compiling strategy and decision making of investment in capital market. In taking decision to conduct a require to be paid attention two matter that is investment risk and return. At securities that have same return, investor try to look for the lower risk. The objectives of this research to analyze the influence of interest rate, trading volume, and exchange rate to sector property stock return that listed on BEI in 2003-2007 periods.This research using time series data from JSX Statistic ICMD (Indonesian Capital Market Directory) and Indonesian Bank monthly published on BEI in January 2003 until December 2006. Population in this research is all company which included in property sector that is 45 companies and number of samples 20 companies by passing phase purposive sample. Analyze technique to use in this research is multiple linier regression to obtain describe which totally regarding relationship between one variable with other variable. The result of this reseacrh shows that interest rate variable has a negative and significant to stock return, while trading volume has positive and not significant to stock return, and than exchange rate have negative significant influence to stock return.